2006
DOI: 10.1111/j.1542-4758.2006.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Online hemodiafiltration: 4 years of clinical experience

Abstract: Online hemodiafiltration (online HDF) is a new hemodialysis technique combining convection and diffusion and thus also enabling the purification of large molecules. As yet, only a small number of clinical experiences have been published about the effectiveness and safety of online HDF. We present a prospective and observational study conducted on 31 patients treated with online HDF in our center in the last 4 years. The purpose of the study is to compare the evolution of the following aspects before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
2
25
2
1
Order By: Relevance
“…Previous studies demonstrated similar benefits (28,29), although such findings are not universal (30,31). It seems that a cooling effect of the infusate may play a major role (31,32).…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies demonstrated similar benefits (28,29), although such findings are not universal (30,31). It seems that a cooling effect of the infusate may play a major role (31,32).…”
Section: Discussionmentioning
confidence: 68%
“…In addition, haemodiafiltration has been reported to improve nutritional parameters and reduce micro-inflammation [19]. Both of which could potentially lead to increased erythropoietin responsiveness, with higher haematocrit and reduced erythropoietin dosages [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing middle molecule clearances, convective treatments have also been reported to improve cardiovascular stability during treatment sessions [7] and reduce the frequency of intradialytic hypotension [8] both with haemofiltration and HDF [8,9]. Other centres have also reported an improvement in interdialytic blood pressure control following the introduction of HDF [10].…”
Section: Introductionmentioning
confidence: 96%